MONITORING DAMAGE AND DAMPNESS IN FLOOD EMBANKMENT BY ELECTRICAL IMPEDANCE TOMOGRAPHY - Rymarczyk, Tomasz; Adamkiewicz, Przemysław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The article presents a model of the measuring system for image reconstruction. Electrical impedance tomography was used to determine the moisture of the test flood blank on a specially built model. The Gauss-Newton methods have been applied very successfully in many areas of the scientific modelling. The basic information about the built model system is given. The finite element method was used to solve the forward problem. The level set method and the Gauss-Newton method were applied to solve the inverse problem.